DELAYS IN BREAST CANCER DIAGNOSIS AT A TERTIARY CARE FACILITY IN KARACHI, PAKISTAN - Hussain, Mahreen; Hasan, Zainab; Ali, Muhammad Ashar; Tapal, Zahra; Saeed, Faizan; Aiman, Wajeeha (Journal of Ayub Medical College Abbottabad, 2021)
Background: Diagnostic delay of breast cancer is linked to poor prognosis and survival. It can be caused by patients or healthcare providers. Since there is no quantification of provider delay and total delay in Pakistan, the general picture of breast cancer diagnostic delay is poorly understood. Objectives: This study was conducted to quantify total delay, provider delay, and patient delay, along with the factors contributing to each type of delay in breast cancer management. Methods: This was a descriptive study conducted over 3 years at a hospital in Karachi. Convenience sampling was used. Breast cancer patients undergoing treatment were interviewed. Values for diagnostic delays extracted from literature were >12 weeks in seeking care as patient delay and >4 weeks in treatment initiation as provider delay. Result: A total of 334 patients were included in the analysis. Mean total delay was 56±52 weeks, the median (IQR) patient delay was 4 (0-22) weeks, and the median provider delay was 17 (9-52) weeks. Patient delay was found in 149 (44.6%), and provider delay was found in 269 (80.5%) patients. Believing symptoms to resolve on their own was the most common reason (24.9%) for patient delay. Seeking multiple opinions (43.7%) and misdiagnosis (43.4%) were the most common reasons for provider delay. Conclusion: Patients and providers both caused diagnostic delay in breast cancer treatment. There is a need to increase awareness in the general population and enhance the training of providers regarding timely recognition in all patients presenting with breast-related symptoms.